Endocrine activity in an urban river system and the biodegradation of estrogen-like endocrine disrupting chemicals through a bio-analytical approach using DRE- and ERE-CALUX bioassays. (June 2018) - Vandermarken, T.; Croes, K.; Van Langenhove, K.; Boonen, I.; Servais, P.; Garcia-Armisen, T.; Brion, N.; Denison, M.S.; Goeyens, L.; Elskens, M.
Abstract: The Zenne River, crossing the Brussels region (Belgium) is an extremely urbanized river impacted by both domestic and industrial effluents. The objective of this study was to monitor the occurrence and activity of Endocrine Active Substances (EAS) in river water and sediments in the framework of the Environmental Quality Standards Directive (2008/105/EC and 2013/39/EU). Activities were determined using Estrogen and Dioxin Responsive Elements (ERE and DRE) Chemical Activated Luciferase Gene Expression (CALUX) bioassays. A potential contamination source of estrogen active compounds was identified in the river at an industrial area downstream from Brussels with a peak value of 938 pg E2 eq./L water (above the EQS of 0.4 ng/L) and 195 pg E2 eq./g sediment. Estrogens are more abundantly present in the sediments than in the dissolved phase. Principal Component Analysis (PCA) showed high correlations between Suspended Particulate Matter (SPM), Particulate (POC) and Dissolved Organic Carbon (DOC) and estrogenic EAS. The dioxin fractions comply with previous data and all were above the United States Environmental Protection Agency (US EPA) low-level risk, with one (42 pg TCDD eq./g sediment) exceeding the high-level risk value for mammals. The self-purifying ability of the Zenne River regarding estrogens was examined with an in vitro biodegradation experiment using the bacterial community naturally present in the river. Hill coefficient and EC50 values (Effective Concentration at 50%) revealed a process of biodegradation in particulate and dissolved phase. The estrogenic activity was decreased by 80%, demonstrating the ability of self-purification of estrogenic compounds in the Zenne River. Graphical abstract: Image 1 Highlights: ERE-CALUX implementation on an urban river with domestic and industrial effluents. Sediment profiles differ significantly for dioxin- and estrogen-like compounds. Estrogenic compounds were found more abundantly in sediments. High correlations between SPM, POC, DOC and estrogenic EAS in water. Dose-response curves of EE2 change drastically during biodegradation.